Integrative taxonomy reveals hidden species within a common fungal parasite of ladybirds - Haelewaters, Danny; De Kesel, André; Pfister, Donald H (Scientific reports, 2018)
Our understanding of fungal diversity is far from complete. Species descriptions generally focus on morphological features, but this approach may underestimate true diversity. Using the morphological species concept, Hesperomyces virescens (Ascomycota, Laboulbeniales) is a single species with global distribution and wide host range. Since its description 120 years ago, this fungal parasite has been reported from 30 species of ladybird hosts on all continents except Antarctica. These host usage patterns suggest that H. virescens could be made up of many different species, each adapted to individual host species. Using sequence data from three gene regions, we found evidence for distinct clades within Hesperomyces virescens, each clade corresponding to isolates from a single host species. We propose that these lineages represent separate species, driven by adaptation to different ladybird hosts. Our combined morphometric, molecular phylogenetic and ecological data provide support for a unified species concept and an integrative taxonomy approach.
Keywords: Sequence Analysis, DNA; mezerníky ribozomální DNA; Animals; DNA fungální; Phylogeny; Ascomycota; brouci; DNA, Ribosomal Spacer; analýza hlavních komponent; zvířata; sekvenční analýza DNA; DNA, Fungal; fylogeneze; Coleoptera; Principal Component Analysis